Do Emotional Laborers Help the Needy More or Less? The Mediating Role of Sympathy in the Effect of Emotional Dissonance on Prosocial Behavior - Park, Yun-na; Hyun, Hyowon; Jhang, JiHoon (Frontiers in Psychology, 2019)
Despite the growing body of research on emotional labor, little has been known about the social consequences of emotional labor. Drawing on emotional dissonance theory, the authors investigate the relationship between the felt emotional dissonance and prosocial behavior (e.g., donation to a charity). Findings from multiple studies suggest that higher emotional dissonance serially influences perceived lack of control, emotional exhaustion, lowered sympathy for others’ feeling, and subsequently lower willingness to help others. When individuals are asked to recall their past experiences of emotional dissonance, they expressed lack of control and emotional exhaustion (Study 3), lower sympathy for others’ feeling (Studies 1, 3), and subsequently become less willing to help others both in their intention (Studies 2A and 3) and with actual money (Study 2B). Further, this negative relationship is moderated by the display rules (i.e., surface acting vs. deep acting, Study 3). Managerial and public policy implications are discussed.